Perancangan Aplikasi Pengembalian Berkas Terhapus Pada NTFS - Rakhmadi Irfansyah Putra; Adith Aulia Rahman (Sekolah Tinggi Teknik - PLN, 2015)
NTFS is a high-performance and self healing file system proprietary to Windows XP Vista 2008 2003 2000 NT & Windows 7,Windows 8, which supports file-level security, compression and auditing. It also supports large volumes and powerful storage solution such as RAID. The most important features of NTFS are data integrity (transaction journal) and the ability to encrypt files and folders to protect your sensitive data. The waterfall development model originates in the manufacturing and construction industries; highly structured physical environments in which after the fact changes are prohibitively costly, if not impossible. Since no formal software development methodologies existed at the time, this hardware-oriented model was simply adapted for software development. File recovery process can be briefly described as drive or folder scanning to find deleted entries in Master File Table (MFT) then for the particular deleted entry, defining clusters chain to be recovered and then copying contents of these clusters to the newly created file.